2013
DOI: 10.1177/1049909113505195
|View full text |Cite
|
Sign up to set email alerts
|

Role Ambiguity, Role Conflict, or Burnout

Abstract: Active hospice volunteers report low levels of role ambiguity, conflict, and burnout. Adopting a range of self-care strategies and working within a structured volunteer program appear to be important protective factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Volunteering in hospice palliative care can be a transformative experience as volunteers come to realize the “gift” they have been blessed with by being able to accompany or “journey” with patients at the end of their lives. These gifts come in many forms, including meaningful conversations and lessons learned as patients open up to them and share life stories, discuss religious topics, and talk about death and what comes next (Planalp et al, 2011), personal growth (Andersson & Ohlen, 2005; Arnup, 2011; Guirguis-Younger & Grafanaki, 2008), gaining valuable life skills (e.g., Letizia et al, 2000), using the skills they (the volunteers) already have (Arnup, 2011), having the privilege of making a difference or positive contribution in the lives of others (Arnup, 2011; Phillips et al, 2013), enhanced self-esteem (Korda, 1995), high levels of personal pride (Jack et al, 2012), forming deep, personal connections with patients and their families (Guirguis-Younger & Grafanaki, 2007), appreciating their own lives more (Arnup, 2011; Guirguis-Younger & Grafanaki, 2007), accepting death as an inevitable part of life and planning for their own death (Wittenberg-Lyles, 2006), and being able to educate others (friends, family members) about death and dying based on their volunteer experiences (Wittenberg-Lyles, 2006). It is no wonder that volunteers often say they get more out of their volunteer experiences than they give.…”
Section: Introductionmentioning
confidence: 99%
“…Volunteering in hospice palliative care can be a transformative experience as volunteers come to realize the “gift” they have been blessed with by being able to accompany or “journey” with patients at the end of their lives. These gifts come in many forms, including meaningful conversations and lessons learned as patients open up to them and share life stories, discuss religious topics, and talk about death and what comes next (Planalp et al, 2011), personal growth (Andersson & Ohlen, 2005; Arnup, 2011; Guirguis-Younger & Grafanaki, 2008), gaining valuable life skills (e.g., Letizia et al, 2000), using the skills they (the volunteers) already have (Arnup, 2011), having the privilege of making a difference or positive contribution in the lives of others (Arnup, 2011; Phillips et al, 2013), enhanced self-esteem (Korda, 1995), high levels of personal pride (Jack et al, 2012), forming deep, personal connections with patients and their families (Guirguis-Younger & Grafanaki, 2007), appreciating their own lives more (Arnup, 2011; Guirguis-Younger & Grafanaki, 2007), accepting death as an inevitable part of life and planning for their own death (Wittenberg-Lyles, 2006), and being able to educate others (friends, family members) about death and dying based on their volunteer experiences (Wittenberg-Lyles, 2006). It is no wonder that volunteers often say they get more out of their volunteer experiences than they give.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been observed that all the volunteers interviewed spoke with enthusiasm about their work alongside caregivers, a result found in other studies, and that some authors explain by the strategies that volunteers use more or less consciously in adapting to stressing situations [39,41]. According to some research, these coping strategies, in association with proper supervision of volunteers by their association, diminish their feeling of burn out and malaise, to the point they do not always view their activities as stressful in spite of the various tensions identified [39,40]. It thus appears that the goodwill with which the volunteers studied fulfill as best they can the missions given them constitutes in itself an important resource for the PCUs as well as for hospices, as Watts also observes for the United Kingdom [2].…”
Section: Palliative Care Volunteers In Pcusmentioning
confidence: 81%
“…While some research has looked at volunteering in general [37,38], other work has been focused totally [21] or partially [1] on volunteer activity as death approaches, and solely from the perspective of volunteers, who are often reticent in discussing the difficulties they encounter in carrying out their missions. Even though international publications in the past 5 years have reported a number of investigations on the volunteer experience in palliative care [2, 17-20, 22, 23], two important questions remain insufficiently studied: (1) that of obstacles and conflicts volunteers may encounter during their activity [39][40][41]; (2) that of the perception that patients, families, and caregivers have of this type of volunteering, whose main challenges we have described above. At most, some authors arrive at the notion of a game where all the actors are winners, with each one gaining a substantial benefit from volunteer activities [24,25], and where volunteers say they are satisfied with their activity (in spite of the tensions noted) [24,39,41].…”
Section: Study Objectivesmentioning
confidence: 99%